Raman spectroscopy a promising technique for investigations of metallothioneins. - Torreggiani, Armida; Tinti, Anna (Metallomics : integrated biometal science, 2010)
Metallobiomolecules are highly elaborated coordination complexes, and their fundamental metal-ligand interactions are critical components of metalloprotein folding, assembly, stability, electrochemistry, and catalytic function. Herein, we have described the benefits in using Raman spectroscopy to define the metal-ion binding properties of MTs toward metal ions such as Zn(ii) and Cd(ii). In particular, this vibrational technique can shed light on the secondary structures eventually present in MTs and the ligands involved in metal coordination. The oxidation state of Cys residues and their participation in the metal chelation can be clearly defined, as well as the eventual involvement of His residues. With regards to exogenous metal ligands such as sulfide anions, their presence can be identified by some marker bands whose intensity is linearly correlated with sulfide/metal molar ratio. Finally, Raman can be also an useful tool for providing information on the favourite sites of the radical attack and radical-induced modification in protein folding. In conclusion, many advantages such as the capability of defining local regions in large complexes and detecting several structural features at the same time, the ability in supporting mechanisms, as well as the requirement of low sample amount, make to propose Raman spectroscopy, in coupling with analytical techniques such as atomic emission spectroscopy, gas chromatography, and circular dichroism, as one of the most promising experimental strategies in the research on structure-activity relationships in MTs.
Keywords: copper; Copper: chemistry; Copper: metabolism; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Spectrum Analysis, Raman; Spectrum Analysis, Raman: methods; Structure-Activity Relationship; Zinc; Zinc: chemistry; Zinc: metabolism

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation